2020
DOI: 10.1088/1755-1315/429/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Variation of seawater temperature and chlorophyll-a prior to and during upwelling event in Bali Strait, Indonesia: from observation and model

Abstract: Coastal upwelling event can be observed clearly from drastic changes of seawater temperature and chlorophyll-a before and during the event. From observation and model output, time-series data of these variables provide important datasets to be used for further analysis, such as developing gaussian empirical model of net marine primary productivity (NPP). Here, the objectives of this study are to analysis variation of temperature and chlorophyll-a (chl-a) from both observation and model output datasets, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The survey generated rich data for the design of the Badung Marine Protected Area and, more broadly, for coastal zone management in the region. We observed a Bryde's whale feeding at an ocean front on 31 October 2015 (Figure 2) and a thermocline-induced upwelling on 1 November 2015 (Figure 6), thus corroborating the knowledge that the southern waters of Bali are still productive in October and early November (Ningsih et al, 2013;Setiawati et al, 2015;Rintaka and Priyono, 2020). Some dolphins and whales were observed quite far from the shoreline (12 nm or 22.2 km, Figures 2-4), indicating that the Badung MPA outer boundary needs to be designed to cover these limits.…”
Section: Cetacean Species Distribution (Objective 2)supporting
confidence: 82%
See 1 more Smart Citation
“…The survey generated rich data for the design of the Badung Marine Protected Area and, more broadly, for coastal zone management in the region. We observed a Bryde's whale feeding at an ocean front on 31 October 2015 (Figure 2) and a thermocline-induced upwelling on 1 November 2015 (Figure 6), thus corroborating the knowledge that the southern waters of Bali are still productive in October and early November (Ningsih et al, 2013;Setiawati et al, 2015;Rintaka and Priyono, 2020). Some dolphins and whales were observed quite far from the shoreline (12 nm or 22.2 km, Figures 2-4), indicating that the Badung MPA outer boundary needs to be designed to cover these limits.…”
Section: Cetacean Species Distribution (Objective 2)supporting
confidence: 82%
“…Seasonal upwellings occur in the western and south western parts of the Bali waters. A 2006-2010 dataset indicated sea surface chlorophyll-a concentrations in this region between April to November (Setiawati et al, 2015), while a 2013 dataset indicated Net Primary Productivity for August to October (Rintaka and Priyono, 2020). Conforming to these literatures, Figure 2 captured the average chlorophyll-a productivity in October 2015 while Figure 3 indicates an upwelling on 1 November 2015.…”
Section: Study Areamentioning
confidence: 95%
“…For example, in the western part of the Indonesian seas, around the western coast of Northern Sumatra, chlorophyll-a ranged from 0.07-0.25 x 10 -3 mg.L -1 (Iskandar et al, 2022). In the south, in the waters of Bali Strait, chlorophyll-a ranged from 0.25-2.25 x 10 -3 mg.L -1 (Rintaka and Priyono, 2020). In unique aquatic ecosystems such as the waters of Kawio Barat submarine volcano, found that the chlorophyll-a ranged from 0.003 to 0.602 x 10 -3 mg.L -1 .…”
Section: Vertical and Horizontal Variability Of Chlorophyll-amentioning
confidence: 99%
“…Even so, the GAM model indicated that optimum water productivity, as shown by the maximum measured chlorophyll-a concentration, was observed at the N:P ratio between 3 and 4 (Figure 4F.). Considering that the chlorophyll-a concentration was comparably high as in some relatively productive waters, such as the Bali Strait (Rintaka and Priyono, 2020), it was suggested that the primary producers in Sangihe-Talaud could still thrive under N-limitation conditions. The unimodal pattern in the response model between chlorophyll-a and N:P ratio (Figure 4F.)…”
Section: Chlorophyll-a Variability and Its Relationship With The Envi...mentioning
confidence: 99%